The 'tumour overkill syndrome'. A potentially lethal complication of cancer chemotherapy. Issue 673 (November 1981) - Slevin, M. L.; Cotterill, A. M.; Bell, R.; Lister, T. A.
Abstract : Two cases of acute leukaemia of Burkitt type in whom chemotherapy was associated with the 'tumour overkill syndrome' are described. One patient died with severe metabolic derangement which followed chemotherapy. In the other, an intensive programme of allopurinol administration, alkalinization of the urine and forced diuresis was instituted before chemotherapy, thus correcting the initial biochemical abnormalities and modifying those which occurred after chemotherapy. This approach prevented a fatal outcome, allowing the patient to survive to achieve bone marrow remission.